Effects of the morphine-lidocaine-ketamine combination on cardiopulmonary function and isoflurane sparing in sheep - Beier, Suzane Lilian; Rosa, Ademir Cassiano da [UNESP]; Oleskovicz, Nilson; Scabelo Mattoso, Claudio Roberto; Dallabrida, Ademar Luiz; Moraes, Aury Nunes de (Univ Estadual Londrina, 2014)
The aims of this study were to evaluate the isoflurane sparing and clinical effects of a constant rate infusion of morphine - lidocaine - ketamine (MLK) in healthy sheep undergoing experimental gastrointestinal surgery. Twelve adult female sheep (Texel breed) were used, weighing 36.5 +/- 8.1 kg. The sheep were anesthetized for the implantation of duodenal cannulas. The sheep were premedicated with 0.3 mg kg(-1) intramuscular (IM) morphine and 20 mu g kg(-1) intravenous (IV) detomidine. After premedication, anesthesia was induced using 5 mg kg(-1) ketamine and 0.5 mg kg(-1) diazepam IV and maintained using isoflurane in 100% oxygen. After the induction of anesthesia, the animals were allocated into two groups (each n=6); the GMLK (MLK group - 10 mg morphine, 150 mg lidocaine, 30 mg de ketamine were added in 500 mL saline) received a 10 mL kg(-1)h(-1) MLK infusion during the maintenance of anesthesia, and GCON (control group) received 10 mL kg(-1)h(-1) of 0.9% sodium chloride. The animals were mechanically ventilated. Cardiopulmonary variables and end-tidal isoflurane concentration (FE'Iso) were measured at baseline (immediately before the surgery) and 15, 30 and 45 minutes after initiation of surgery. In GMLK, there was a decrease in the FE 'Iso at 15, 30 and 45 minutes, a reduction of up to 75.6% during the surgery. The HR was lower in GMLK compared with GCON at 30 minutes, and the MAP was at during baseline in GCON compared with GMLK. The standing time was less in GMLK than in GCON. The use of intravenous MLK was demonstrated to offer great efficiency as part of a balanced anesthesia protocol in sheep, with a 75.6% reduction in the need for isoflurane, providing stability of the cardiovascular parameters and blood gases with a shortened recovery period.

Os objetivos deste estudo foram avaliar a redução na concentração expirada de isoflurano, bem como os efeitos clínicos de uma infusão constante de morfina – lidocaína – cetamina (MLK) em ovinos saudáveis submetidos a cirurgia gastrointestinal experimental. Foram utilizados doze ovinos adultos da raça Texel, fêmeas, pesando 36,5 ± 8,1 kg. Os animais foram anestesiados para implantação de cânulas no duodeno, sendo pré-medicados com morfina 0,3 mg kg-1, pela via intramuscular (IM), e detomidina 20 ug kg- 1 pela via intravenosa (IV). Após a pré-medicação, a anestesia foi induzida com cetamina 5 mg kg –1 e diazepam 0,5 mg kg –1 IV, sendo mantidos com isoflurano em oxigênio a 100%. Após a indução da anestesia os animais foram divididos em dois grupos (n = 6): GMLK (grupo MLK – 10 mg de morfina, 150 mg de lidocaína e 30 mg de cetamina foram adicionados em 500 ml de solução salina) que recebeu infusão contínua de MLK na taxa de 10 mL kg– 1h-1 durante a manutenção da anestesia; e o GCON (grupo de controle) que recebeu infusão contínua de cloreto de sódio a 0,9% na taxa de 10 mL kg– 1h-1 durante a manutenção da anestesia. Os animais foram submetidos à ventilação mecânica. As variáveis cardiopulmonares e concentração de isoflurano ao final da expiração (FE’Iso) foram avaliados durante o momento basal (imediatamente antes da cirurgia), e 15, 30 e 45 minutos após o início da cirurgia. Em GMLK ocorreu uma redução na FE’Iso aos 15, 30 e 45 minutos, sendo observada redução de até 75,6 % durante a cirurgia. A FC foi menor no GMLK em comparação ao GCON aos 30 minutos, e a PAM foi menor no momento basal no GCON em relação ao GMLK. O tempo de recuperação total foi menor no GMLK. O uso da infusão contínua intravenosa da solução MLK mostrou ser eficiente como parte de um protocolo de anestesia balanceada em ovinos, com uma redução de 75,6 % na concentração expirada de isoflurano, proporcionando estabilidade cardiovascular e com um período de recuperação reduzido.
Efeito da associação de morfina-lidocaína-ketamina sobre a função cardiopulmonar e concentração expirada de Isoflurano em ovelhas
Keywords: Sheep; Morphine; Lidocaine; Ketamine; Isoflurane; Ovino; Morfina; Lidocaína; Cetamina; Isoflurano